Getting out of mitosis: Spatial and temporal control of mitotic exit and cytokinesis by PP1 and PP2A - Holder, J; Poser, E; Barr, F (Wiley, 2019)
Here, we will review the evidence showing that mitotic exit is initiated by regulated proteolysis and then driven by the PPP family of phosphoserine/threonine phosphatases. Rapid APC/CCDC 20 and ubiquitin-dependent proteolysis of cyclin B and securin initiates sister chromatid separation, the first step of mitotic exit. Because proteolysis of Aurora and Polo family kinases dependent on APC/CCDH 1 is relatively slow, this creates a new regulatory state, anaphase, different to G2 and M-phase. We will discuss how the CDK1-counteracting phosphatases PP1 and PP2A-B55, together with Aurora and Polo kinases, contribute to the temporal regulation and order of events in the different stages of mitotic exit from anaphase to cytokinesis. For PP2A-B55, these timing properties are created by the ENSA-dependent inhibitory pathway and differential recognition of phosphoserine and phosphothreonine. Finally, we will discuss how Aurora B and PP2A-B56 are needed for the spatial regulation of anaphase spindle formation and how APC/C-dependent destruction of PLK1 acts as a timer for abscission, the final event of cytokinesis.